Immigration, Housing Discrimination and Employment - Tito Boeri; Marta De Philippis; Eleonora Patacchini; Michele Pellizzari (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
We use a new dataset on eight Italian cities and a novel identification strategy to analyze the relationship between the employment status of migrants and the percentage of migrants living nearby. Our data contain information at the very local level (i.e. the residential block) and are representative of the population of both legal and illegal migrants. Identification is based on an instrumental variable strategy that exploits the physical characteristics of the local buildings as a source of exogenous variation in the incidence of migrants in each location. We find evidence that migrants who reside in areas with a high concentration of non-Italians are less likely to be employed compared to similar migrants who reside in more mixed areas. This penalty is higher if the migrants leaving nearby are illegal and it is not mitigated by living close to migrants who are from own's ethnic group nor who are more proficient in the Italian language. The employment prospects of natives do not appear to be affected by the vicinity of migrants.
Keywords: J15; J61; R23; 330; Immigrant residential density; housing discrimination; ethnic networks